LAPAROSCOPIC FUNDAPLICATIONS GASTROOESOPHAGEAL REFLUX DISEASE TREATMENT - Veligozkiy, N.N.; Gorbulich, A.V.; Komarchuck, V.V.; Veligozkiy, A.N.; Trushin, A.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The results of modified laparoscopic fundoplications in 7 patients with the gastroesophageal reflux disease are described. Indications for each modified fundoplication method were discussed. An analysis of the operation results has shown effectiveness and safety of using the modified methods by laparoscopic approach.